PemBla: A Phase 1 study of intravesical pembrolizumab in recurrent non‐muscle‐invasive bladder cancer. Issue 3 (13th January 2023) - Woodcock, Victoria K.; Chen, Ji‐Li; Purshouse, Karin; Butcher, Chrissie; Collins, Linda; Haddon, Caroline; Verrall, Gillian; Elhussein, Leena; Roberts, Corran; Tarlton, Andrea; Rei, Margarida; Napolitani, Giorgio; et al.
Abstract: Objectives: This study aimed to investigate the anti‐PD‐1 inhibitor pembrolizumab as a potential agent for use in non‐muscle‐invasive bladder cancer (NMIBC) by conducting a Phase 1 safety run‐in study to assess the safety and tolerability of intravesical pembrolizumab after transurethral resection of the bladder tumour (TURBT). Patients and methods: Eligible patients had recurrent NMIBC for which adjuvant treatment post TURBT was a reasonable treatment option, Eastern Cooperative Oncology Group Performance Status (ECOG PS) 0–1 and adequate end‐organ function. Pembrolizumab was administered by intravesical instillation once weekly for a total of six doses. Intra‐patient dose escalation was performed in three paired patient cohorts with doses starting at 50 mg and increasing through 100 mg to a maximum of 200 mg. Adverse events (AEs) were assessed using Common Terminology Criteria for Adverse Events (CTCAE) v4.03 with dose limiting toxicity (DLT) defined as a clinically significant, drug‐related, Grade 4 haematological or Grade 3 or higher non‐haematological toxicity occurring within 7 days of administration of the first treatment at a given dose for that patient. Results: Six patients were treated with no DLTs seen during dose escalation. Drug‐related AEs were of low grade and included dysuria and fatigue. All patients completed six doses of treatment as planned. Pharmacokinetic and pharmacodynamic assays did not detect any pembrolizumab in the serum following repeated intravesical administration, and no changes in peripheral immune cell populations were observed. Conclusions: Administration of intravesical pembrolizumab was well tolerated and did not raise any safety concerns in patients with NMIBC following TURBT. There was no evidence of systemic absorption or systemic immune effects following intravesical administration. Further studies are required to assess whether intravesical administration has anti‐tumour activity.